THE PROSEDURE FOR ORGANIZING THE ANALYSIS OF FINANCIAL STATEMENTS IN BANKS (World Economics and Finance Bulletin, 2023)
This article outlines a systematic procedure for organizing the analysis of financial statements in banks. The aim is to provide a comprehensive framework that enhances the efficiency and effectiveness of financial statement analysis, aiding in informed decision-making. The article covers key elements such as the introduction of the analysis, the methods employed, results obtained, a detailed discussion, and conclusive recommendations for better financial management
Keywords: Financial Statements; Banking Analysis; Organizational Framework